THE EFFECT OF TRUST, SATISFACTION AND VALUE PERCEPTION ON CONSUMER LOYALTY IN PURCHASING ALFAMART PRODUCTS IN LHOKSEUMAWE CITY - Ariana Hasibuan; Heriyana Heriyana; Jullimursyida Jullimursyida; Khairina AR (Jurnal Intelek Insan Cendikia, 2025)
Abstract this research aims to determine the extent to which consumers in Lhokseumawe City influence consumer loyalty when choosing to purchase Alfamart products. The population in this study consists of consumers who have purchased products at Alfamart. The sample consists of 105 respondents. The primary data consists of questionnaire results distributed to the research respondents. This study uses a quantitative approach with multiple linear regression analysis and is processed using the SPSS (Statistical Package for the Social Sciences) software. The hypothesis was determined using SPSS version 25.0. The results of this study indicate that, partially, the Trust variable has a positive and significant effect on Customer Loyalty, statistically 0.000 < 0.04, and has a t-value > t-table, 2.912 > 1.660. The Satisfaction variable has a significant positive effect on Customer Loyalty, statistically 0.002 < 0.05, with a t-value > t-table, 2.985 > 1.660. Then, the Perceived Values variable has a positive and significant effect on Customer Loyalty, statistically 0.001 < 0.05, and has a t-value > t-table, namely 3.333 > 1.660. The adjusted R-square value for the independent variables—Trust, Satisfaction, and Perceived Value—indicates that 37.7% is explained by these variables, while the remaining 62.3% is explained by other variables not included in this study.